Ground layer depth and the effect of GPR - A. Puttarach (2018)
This paper presents a substation grounding grid analysis with the variation of soil layer depth. The grounding grid system of a practical 22 kV substation, in which the ground grid is made from copper, is calculated by virtue of the CDEGS software. The study, supported by Provincial Electricity Authority (PEA), Thailand, is based on grounding grid system of Royal Flora RATCHAPHRUEK substation. The supporting soil resistivity data has been obtained from field tests at the substation. The result shows that soil resistivity was interpreted to two-layer soil structure with low resistivity top layer and high resistivity bottom layer. The studied ground grid system is installed with constant 3 m ground rods. When the ground layer depth of the grid is increased, it directly affects to reduce the value of Ground Potential Rise (GPR). On the other hand, with the same grid configuration buried in the high resistivities bottom layer, its GPR is not reduced, that is, the more layer depth of high resistivities bottom layer, the more value of GPR. In addition, the grid with the different ground rods length also gives the different results. GPR is continuously reduced when the rod length is lengthened even though the bottom layer resistivity is higher than the top layer. © 2008 ICQR.